High prevalence of Wilms tumor 1 expression in multiple myeloma and plasmacytoma: A cohort of 142 Asian patients' samples - Ployploen Phikulsod; Ployploen Phikulsod; Ployploen Phikulsod; Sanya Sukpanichnant; Chutima Kunacheewa; Thaweesak Chieochansin; Mutita Junking; Pa-Thai Yenchitsomanus (Frontiers Media S.A., 2023)
Wilms tumor 1 (WT1) is a promising target antigen for cancer immunotherapy. However, WT1 protein expression and its clinical correlation in multiple myeloma (MM) patients are still limited. We, therefore, investigated WT1 expression in 142 bone marrow and plasmacytoma samples of MM patients at different stages of the disease by immunohistochemistry. The correlations between WT1 expression and clinical parameters or treatment outcomes were evaluated. The overall positive rate of WT1 expression was 91.5%; this high prevalence was found in both bone marrow and plasmacytoma samples, regardless of the disease status. Cytoplasmic WT1 expression was correlated with high serum free light chain ratio at presentation. However, no significant association between WT1 expression and treatment outcome was observed. This study confirms the high prevalence of WT1 expression in an Asian cohort of MM, encouraging the development of immunotherapy targeting WT1 in MM patients, particularly in those with extramedullary plasmacytoma or relapsed disease.